Innovation of Sonia Handcraft Lace Products in Bukik Ngalau Padang - Nauren Maisarah; Asmidar (International Journal For Advanced Research, 2025)
This study aims to describe and analyze product innovation carried out by UMKM Sonia Handcraft in developing lace crafts in Bukik Ngalau, Sonia Handcraft is a micro-enterprise engaged in handicrafts, especially products made from lace, such as bags, decorations, and household accessories. In facing market competition and the development of consumer trends, business actors are required to continue to innovate in terms of design, function, and marketing. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and documentation. The results of the study show that Sonia Handcraft has succeeded in developing product innovation by adding aesthetic value, combining modern materials with traditional lace, and more attractive product packaging. The innovations carried out not only maintain local cultural values, but also increase product competitiveness in local and regional markets. The conclusion of this study shows that innovation is an important factor in the sustainability and development of craft-based MSMEs